Tocilizumab for steroid refractory acute graft-versus-host disease - Roddy, Julianna V. F. (Leuk Lymphoma, 2015)
Acute graft-versus-host-disease (aGVHD) is a frequent and often lethal complication of allogeneic hematopoietic stem cell transplant despite prophylaxis. Tocilizumab is a humanized anti-IL-6 receptor monoclonal antibody that has evidence of activity in patients with steroid refractory (SR) GVHD. We retrospectively report on nine patients with grade 3 or 4 SR aGVHD who received tocilizumab. Eight mg/kg of tocilizumab was administered intravenously every 3–4 weeks. aGVHD grading and responses were based on consensus criteria. Median age at transplant was 48 years. Five patients had alternate donor sources. Median time from aGVHD onset to tocilizumab administration was 44 days. Two patients had complete responses and two had partial responses. Median survival from start of tocilizumab was 26 days (range 13–1054). Our limited experience demonstrated an overall response rate of 44% (CR + PR); however, this response was not durable. Further studies are needed to determine the optimal time for tocilizumab initiation.